2009
DOI: 10.1007/s10530-009-9450-3
|View full text |Cite
|
Sign up to set email alerts
|

Brown trout (Salmo trutta) invasiveness: plasticity in life-history is more important than genetic variability

Abstract: Brown trout of German origin were introduced into Patagonian National Parks in 1905, where they acclimatized and underwent population expansion endangering populations of native species like Galaxiidae. Spawning adults of two populations were sampled in 2004. Their age, length-at-age and migratory behaviour were assessed from scale samples, as well as their variation at the coding LDH-C1* and eight non coding microsatellite loci. Betweenpopulation differentiation for life history (spawning time, migratory beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…A paradox often encountered in genetic studies of invasive species, is a colonization success of the introduced populations despite a strong reduction of genetic diversity (Frankham 2005; see also reviews by Dlugosch andParker 2008 andRoman andDarling 2007). Several studies to date have shown that founder effects and bottlenecks are not an obstacle for invasion success (Ahern et al 2009;Puillandre et al 2008;Solignac et al 2005), whereas plasticity in life history traits seems to be important for the successful expansion of an invasive species (Chen et al 2006;Valiente et al 2010;Wang et al 2005). Mites belonging to clade I have been found across a wide range of habitats and regions beyond the predicted geographical distribution as modeled based on climatic suitability T. evansi ).…”
Section: Species-wide Genetic Homogeneity and Invasion Eventsmentioning
confidence: 99%
“…A paradox often encountered in genetic studies of invasive species, is a colonization success of the introduced populations despite a strong reduction of genetic diversity (Frankham 2005; see also reviews by Dlugosch andParker 2008 andRoman andDarling 2007). Several studies to date have shown that founder effects and bottlenecks are not an obstacle for invasion success (Ahern et al 2009;Puillandre et al 2008;Solignac et al 2005), whereas plasticity in life history traits seems to be important for the successful expansion of an invasive species (Chen et al 2006;Valiente et al 2010;Wang et al 2005). Mites belonging to clade I have been found across a wide range of habitats and regions beyond the predicted geographical distribution as modeled based on climatic suitability T. evansi ).…”
Section: Species-wide Genetic Homogeneity and Invasion Eventsmentioning
confidence: 99%
“…There are several difficulties in identifying the biological attributes that can be used to predict the invasive potential of an introduced fish species. Fish are known to have high phenotypic plasticity (Wooton 1990), with plasticity of their life-history traits more important for invasion success than their genetic variation (Valiente et al 2010). Life histories may be modified as the population passes through a series of stages of invasion (Bøhn et al 2004;Fox et al 2007;Britton et al 2008;Brandner et al 2013b), with different traits important during distinct stages of the invasion process (Ribeiro et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Decision-making rules, also named "Darwinian algorithms" (Cosmides & Tooby, 1987), are predicted to be adaptive, since they depend on cues that might change over evolutionary time, interfering in the survival and reproductive success of species (Williams & Nichols, 1984). Particularly important, are some biological aspects (e.g., intense reproductive activity, biparental care of eggs and capability of adaptation to harsh ecological conditions) that make Cichla a potential invasive apex predator (Munoz et al, 2006;Resende et al, 2008;Vieira et al, 2009;Zaret, 1980), as also shown for the brown trout introduced in Patagonia (Valiente et al, 2010).…”
Section: Since Neutral Genetic Diversity Appear Unimportant In Cichlamentioning
confidence: 93%
“…Similar results were observed for the brown trout (Salmo trutta) introduced into Patagonia National Parks (Argentina). In this case, plasticity in life-history such as flexibility in migratory behavior and spawning, seem to be more important to the invasive process than genetic variability (Valiente et al, 2010).…”
Section: Pristine Vs Impacted Sitesmentioning
confidence: 99%
See 1 more Smart Citation